Medieval Studies in Honor of Urban Tigner Holmes, Jr. - Keller, John Esten; Mahoney, John (Studies in the Romance languages and literatures ;, 2019)
This volume is composed of articles by former students of Professor Holmes and presented to him in his sixty-fifth year. Most of the essays deal with medieval subjects or subjects very closely associated with the Middle Ages.